Formulation and Evaluation of Soursop (Annona muricata) Leaf Extract Nanoemulgel Against Propionibacterium acnes - Ikramina, Nabila; Rehana, Rehana; Prasetya, Rahmad Aji; Kurniawan, Dhadhang Wahyu (Borneo Journal of Pharmacy, 2024)
Annona muricata (soursop) leaves are rich in antimicrobial compounds such as flavonoids, alkaloids, tannins, saponins, and phenols. This study aimed to develop a nanoemulgel formulation incorporating A. muricata leaf ethanol extract to enhance its efficacy against Propionibacterium acnes, a bacterium associated with acne vulgaris. Four nanoemulgel formulations containing varying concentrations of the extract (0%, 0.5%, 0.7%, and 1%) were prepared and evaluated for their physical properties (organoleptic, homogeneity, pH, spreadability, and viscosity) and stability through freeze-thaw cycles. The formulation with the highest extract concentration (Formula III) was selected for further characterization (particle size, morphology, and zeta potential) and antimicrobial testing against P. acnes. All formulations met the established physical property and stability criteria. Formula III exhibited a particle size of 20.5 nm and a zeta potential of 9.8 mV, indicating a stable nanoemulsion with well-dispersed particles. Antimicrobial testing revealed that Formula III demonstrated a strong inhibitory effect against P. acnes, with an average inhibition zone of 19.00 mm. These findings suggest that A. muricata leaf extract-loaded nanoemulgel has the potential to be a promising topical formulation for acne treatment. Further research is warranted to optimize the formulation and evaluate its efficacy in clinical settings.